TEKNIK BUTEYKO UNTUK MENGATASI MASALAH POLA NAFAS TIDAK EFEKTIF PADA PASIEN ASMA DI IGD - Ahmad Muzaki (STIKES Pemkab Purworejo, 2023)
Background Asthma is an episodic and reversible obstructive airway disease in which a trigger can cause an overactive response of the trachea and bronchi. Asthma also causes wheezing, shortness of breath, and coughing. The prevalence of asthma in Indonesia, based on the results of Riskesdas 2018, is 24% of the population of all ages, while the rate is 1.77%. The objective of this case study was to provide nursing care to asthmatic clients with breastfeeding problems and poor respiratory problems at Prembun IGD hospital. This method uses descriptive method using case study method. The defendants in this case study are Ms. K and Ms. Mis. The M in the case of this study is also the same when observation, measurement, interview or history, physical examination, and recording are used concurrently for the same data source. Results were also obtained in patients whose breathing patterns were not effective with the Buteyko Able Client technique. The client performed the Buteyko Technique to achieve two results: regular breathing adjustments and increased oxygen saturation. The conclusion was that the Buteyko technique in asthmatic patients was more effective in correcting breathing patterns